The Role Of Models In Computer Science. - Fetzer, James H. (Monist, 1999)
Explores the role of models in computer science. Specifications as models of problems; Programs as models of possible solutions; Existence of conceptualizations as ways of conceiving the world; High-level programming languages as models of virtual machines; Low-level programming languages as models of causal machines; Indispensability of models embedded within models for computer programming.